Fridericia platyphylla (Cham.) L.G. Lohmann root extract exerts cytotoxic and antiproliferative effects on gastric tumor cells and downregulates BCL-XL, BIRC5, and MET genes - Serpeloni, J. M. [UNESP]; Specian, A. F.L.; Ribeiro, D. L.; Benício, L. M.; Nunes, H. L.; Franchi, L. P.; Rocha, C. Q.; Vilegas, W. [UNESP]; Varanda, E. A. [UNESP]; Cólus, I. M.S. [UNESP] (SAGE Publications, 2020)
Fridericia platyphylla (Cham.) L.G. Lohmann (FP) has cytotoxic, anti-inflammatory, and analgesic properties. We aimed to characterize the cytotoxic and antiproliferative effects of FP extract on normal (GAS) and tumor-derived (ACP02 and HepG2) cell lines. The effective concentrations (EC50s) by tetrazolium bromide assay (MTT) were 56.16, 43.68, and 42.57 µg mL−1 and 69.38, 41.73, and 52.39 µg mL−1 by neutral red assay for GAS, ACP02, and HepG2 cells, respectively. The extract decreased nuclear division indices, which was not reflected in cell proliferation curves. Flow cytometric analyses showed that even 30 µg mL−1 extract (shown to be noncytotoxic by MTT assay) increased the sub-G1 population, indicating cell death due to apoptosis and necrosis. A cytokinesis-block micronucleus cytome assay showed that 30 µg mL−1 of the extract increased the frequency of nuclear buds in tumor cells. Real-time quantitative polymerase chain reaction showed CCND1 upregulation in doxorubicin-treated GAS cells and BCL-XL, BIRC5, and MET downregulation in 5 or 30 µg mL−1 in FP extract-treated ACP02 cells. In conclusion, FP extract modulated apoptosis- and cell cycle-related genes and presented selective cytotoxicity toward tumor cells that deserves further investigation by testing other cell types. Our results demonstrated that even medicinal plants exert adverse effects depending on the extract concentrations used and tissues investigated.
Keywords: Antiproliferative; apoptosis; Fridericia platyphylla; gastric cells; NBUDs